Household as a Unit of Changing Social Structure - Sigdel, Bhim Raj (Journal of Development Review, 2024)
Almost all the comparative historical analysis have been done from etic perspective that always describes the external social structure as the determinant of social change especially in changing internal structure like households. However, this study tries to describe, the external as well as internal, both factors of society contribute for the transformation of households. In this context, two major questions have been raised. First, what are the major events that shaped my own household since last twenty years? And the second, how do those events contribute to transform the household as a unit of social structure? This study is based on lived experiences and group discussions supplemented through unobtrusive measure within family gatherings that are attributed as data required for the comparative historical analysis of household in a twenty year long run. It explores five major events within a household that contribute for its transformation. Eventually, it finds that both internal and external factors that contribute to occur as events of a household transformation at structural level. As capitalist neo-liberal structure is being developed rapidly, structure and attributes of household have been changing along with its pace; at the same time, internal factors (adaptive nature) such as idea of surplus cattle, migration from rural to urban, adaptation of urban life, transformation of occupation, division of family, international migration etc. are also playing crucial roles to shape households in substantive ways.